What decisions can women make in Banke, Nepal? Women’s agency and perceptions of domestic violence - Chauhan, Alka; Kumar, Neha; Quisumbing, Agnes R.; Banerjee, Archis; Tomar, Anindya; Scott, Samuel P.; Menon, Purnima; Kishore, Avinash (CGIAR System Organization, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a multi-year assessment. Using data collected in March–April 2023, this data note describes women’s say or agency in various household decisions, their physical and financial independence, their mobility, and their perceptions of domestic violence. This is one of a set of data notes that, together, provide a holistic picture of theagrifood system in the district.